Astronomy in Georgia - Chargeishvili, B. B.
We provide a brief history of Georgian astronomy and discuss its current state. The discussion also covers the scientific facilities of Georgia’s leading astrophysical institute, the Evgeni Kharadze Georgian National Astrophysical Observatory, as well as current scientific projects and specialists involved in them. It also includes educational activities on astronomy in Georgia.
Keywords: Astronomy; Georgia